Gender difference in mobile phone use and the impact of digital device exposure on neck posture. Issue 11 (1st November 2016) - Guan, Xiaofei; Fan, Guoxin; Chen, Zhengqi; Zeng, Ying; Zhang, Hailong; Hu, Annan; Gu, Guangfei; Wu, Xinbo; Gu, Xin; He, Shisheng
Abstract: This cross-sectional study aimed to identify gender differences in the cervical postures when young adults were using mobile phones, as well as the correlations between the postures and the digital devices use (computer and mobile phone). Questionnaires regarding the habits of computer and mobile phone use were administrated to 429 subjects aged from 17 to 33 years old (19.75 ± 2.58 years old). Subjects were instructed to stand habitually and use a mobile phone as in daily life; the sagittal head and cervical postures were measured by head flexion, neck flexion angle and gaze angle. Male participants had a significantly larger head flexion angle (96.41° ± 12.23° vs. 93.57° ± 12.62°, p   =  0.018) and neck flexion angle (51.92°  ±  9.55° vs. 47.09° ± 9.45°, p   <  0.001) than females. There were significant differences in head ( F   =  3.62, p   =  0.014) and neck flexion ( F   =  3.99, p   =  0.009) between different amounts of computer use. Practitioner Summary : We investigated possible gender differences in head and neck postures of young adults using mobile phones, as well as the potential correlations between these postures and digital device use. We found that males displayed larger head and neck flexion angles than females, which were associated with the amount of computer use.